2003
DOI: 10.1302/0301-620x.85b5.13812
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cruciate ligament at total knee replacement

Abstract: e report the results of a prospective randomised trial which assessed the role of the posterior cruciate ligament (PCL) following total knee replacement (Genesis I; Smith and Nephew, Memphis, Tennessee). Over a four-year period, 211 patients underwent total knee replacement by the senior author (TJW). They were randomised at surgery to have the PCL either retained, excised or substituted with a posterior stabilised insert. If it was not possible to retain the ligament due to soft-tissue imbalance, it was relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 12 publications
(13 reference statements)
5
62
0
1
Order By: Relevance
“…One study also showed that the time to first analgesic request was significantly longer with parecoxib compared with placebo [14] (see Table 1). [19] Inconclusive Ropivacaine via femoral catheter [117] NS Bupivacaine via femoral catheter [35] NS Spinal diamorphine [42] NS Spinal morphine [43] NS Lumbar epidural ketamine [52] NS Lumbar epidural ropivacaine [50,53] Inconclusive Route and method of drug administration IV vs IM strong opioid [23] NS IV PCA vs IM strong opioid [24] IM superior for moderate pain scores Surgical approaches Medial trivector approach [61], Subvastus approach [62], vs parapatellar approach NS Posterior cruciate ligament (PCL) surgery during TKA: different surgical approaches [63] PCL released surgery inferior to other approaches Midvastus approach vs medial parapatellar approach [64] Midvastus superior at rest and on movement…”
Section: Cox-2-selective Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study also showed that the time to first analgesic request was significantly longer with parecoxib compared with placebo [14] (see Table 1). [19] Inconclusive Ropivacaine via femoral catheter [117] NS Bupivacaine via femoral catheter [35] NS Spinal diamorphine [42] NS Spinal morphine [43] NS Lumbar epidural ketamine [52] NS Lumbar epidural ropivacaine [50,53] Inconclusive Route and method of drug administration IV vs IM strong opioid [23] NS IV PCA vs IM strong opioid [24] IM superior for moderate pain scores Surgical approaches Medial trivector approach [61], Subvastus approach [62], vs parapatellar approach NS Posterior cruciate ligament (PCL) surgery during TKA: different surgical approaches [63] PCL released surgery inferior to other approaches Midvastus approach vs medial parapatellar approach [64] Midvastus superior at rest and on movement…”
Section: Cox-2-selective Inhibitorsmentioning
confidence: 99%
“…Four studies were included that compared different surgical approaches for TKA surgery [61][62][63][64], but the results were inconclusive in terms of pain scores (see Table 2) given the limited number of studies for each technique.…”
Section: Surgical Approachmentioning
confidence: 99%
“…PCL-retaining designs have been shown to be associated with a limited increase in the range of flexion (in comparison with PCL-substituting designs) in certain studies, [3][4][5][6] while no such increase in flexion has been found by others. [7][8][9] Studies which have found increase in flexion have attributed it to higher femoral roll back in PCL-retaining designs. The increased roll back is also said to increase the quadriceps lever arm and the power of extension.…”
Section: Introductionmentioning
confidence: 99%
“…During surgery, unintended injury to the PCL often occurs by resection of the proximal tibia [17]. Additional PCL injuries can occur during an attempt to equalise flexion and flexion after resection of the articular ends of the bones forming the knee joint, which is a difficult technique [20]. If the PCL is too tensed, the flexion space is less than the extension space.…”
Section: Discussionmentioning
confidence: 99%